THE EFFECT OF THE USE OF CLOUD ARTIFICIAL INTELLIGENCE ON IMPROVING THE QUALITY OF THE AUDITOR'S REPORT - Dr. Mohammed Frayyeh Hassan (Scholar Express Journals, 2023)
The business environment in this period witnessed a set of technological developments, especially in information systems, which led to this development to change changes represented in the transformation from traditional systems to digital systems, which in turn affected the financial, administrative and operational aspects in all departments. Therefore, the goal of research is to explain the relationship of the use of cloud artificial intelligence with the process of review and the important role that the references experience in planning and implementing the review process in light of the review customers of the review of cloud computing technology in preserving and storing data and indicating the effect of the references process to obtain evidence that helps him in arrival To a neutral technical opinion and the completion of the report at the appropriate time and submitting it to decision -makers at the appropriate time to make appropriate decisions.
Keywords: cloud artificial intelligence; cloud computing; digital transformation